Diffusion, adoption and non-adoption of ABC in a developing country: case study evidence from Sri Lanka / Harin de Silva - de Silva, Harin (2009)
The paper discusses the adoption of ABC and the role played by consultants, academics and the profession, in propagating ABC in a developing country, Sri Lanka. Further the influences of the supply side of the information field, the cultural factors and how A BC is constituted in organisations is discussed. Interviews were conducted on consultant some users, and prospective adopters of ABC. The factor such as lhe size of the organisation, uncertainty in the socio-political and the economic environment, cost-benefit of implementation, innovation, competition in the economic environment, the information field and the cultural influences that the organisations are subject to have influenced the adoption of ABC.